2019
DOI: 10.1002/hpja.235
|View full text |Cite
|
Sign up to set email alerts
|

Addressing nutrition and social connection through community gardening: A South Australian study

Abstract: Background This research aimed to evaluate the benefits of the community gardening program called ‘‘Magic Harvest (MH)” with respect to its key elements: social interaction; gardening skills; and, healthier eating. The MH program supports community participants to grow food, share produce, prepare and preserve food. Methods Two focus groups were conducted with participants in MH programs in the south of Adelaide, South Australia. The MH programs were located in lower socio‐economic areas. Focus group interview… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Social engagement and positive dietary changes were also reported by Kaye Mehta and colleagues through community gardening with participants reporting the consumption of a wider variety of fruit and vegetables. A scoping review of community initiatives and interventions associated with vegetable intake identified the opportunity for community‐driven initiatives within local food systems to increase vegetable consumption and a potential to build healthy public policy.…”
mentioning
confidence: 72%
“…Social engagement and positive dietary changes were also reported by Kaye Mehta and colleagues through community gardening with participants reporting the consumption of a wider variety of fruit and vegetables. A scoping review of community initiatives and interventions associated with vegetable intake identified the opportunity for community‐driven initiatives within local food systems to increase vegetable consumption and a potential to build healthy public policy.…”
mentioning
confidence: 72%